The prognostic significance of positive peritoneal cytology in endometrial cancer and its correlations with L1-CAM biomarker. (March 2019) - Vizza, Enrico; Mancini, Emanuela; Laquintana, Valentina; Loria, Rossella; Carosi, Mariantonia; Baiocco, Ermelinda; Cicchillitti, Lucia; Piaggio, Giulia; Patrizi, Lodovico; Sperduti, Isabella; Zampa, Ashanti; Cutillo, Giuseppe; et al.
Abstract: Background: The aim of this study was to evaluate the prognostic role of positive peritoneal cytology (PPC) in a cohort of patients with endometrial cancer (EC). The secondary objective was to correlate the PPC and the expression of L1CAM in a group of patients with recurrence endometrial disease. Methods: All women diagnosed with EC and who performed a peritoneal cytology at "Regina Elena" National Cancer Institute of Rome from 2001 to 2013 were included in the study. Patients were divided into two groups according to positivity at peritoneal cytology. Moreover, patients with a recurrence disease and whose a tissue microarray (TMA) tumor sample was available underwent a L1CAM analysis. Results: Seven hundred sixty six patients underwent to EC staging in our Institute: 696 (90.8%) with negative and 70 (9.2%) with positive cytology. Five-year recurrence rate was higher in women with PPC (46.9% vs 18.4%, p = 0 < 0.0001) and, in particular, distant recurrence (86.7% vs 53.4%, p = 0.03). Moreover, we found an interesting pattern of recurrence disease in the group of early stage of EC with NPC and positive L1CAM. Conclusions: Our results support the data that PPC may be a potential prognostic factor in early EC, due to its significant association with other risk factors and its significant influence on survival. Our findings confirm the need for large studies that point out the role of PPC and new prognostic factors, including biomarkers as L1CAM. Highlights: Peritoneal positive cytology could be an independent risk factor for endometrial cancer prognosis. L1CAM are related to tumor progression. Peritoneal positive cytology and L1CAM could be a potential additional tool for endometrial cancer stratification.